2004
DOI: 10.1212/01.wnl.0000140487.55973.d7
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of famous faces in the medial temporal lobe

Abstract: The anterior medial temporal lobe N400 and the hippocampal P600 may be related to the access and retrieval of person-specific semantic memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 29 publications
8
37
2
Order By: Relevance
“…Consistent with this interpretation, a recent study reported that real object induced a large P600, whereas nonsense objects induced no P600 (Vannucci et al, 2003). In another study, this wave was found to be larger for famous as compared with nonfamous faces (Trautner et al, 2004). Both studies suggested that objects with rich semantic associations activated the hippocampus.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with this interpretation, a recent study reported that real object induced a large P600, whereas nonsense objects induced no P600 (Vannucci et al, 2003). In another study, this wave was found to be larger for famous as compared with nonfamous faces (Trautner et al, 2004). Both studies suggested that objects with rich semantic associations activated the hippocampus.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to this role in memory processing, the P600 may also reflect more general semantic processing. This was suggested by findings of a larger P600 for real objects than for nonsense objects (Vannucci et al, 2003), and a larger P600 for famous faces than nonfamous faces (Trautner et al, 2004). Thus, the P600 might reflect associative processing of items in both memory encoding and continuous recognition tasks.…”
Section: Methodsmentioning
confidence: 96%
“…This is somewhat surprising given the stable fame effects typically observed in ERP (Begleiter et al, 1995;Trautner et al, 2004). Two things may be at play here.…”
Section: Discussionmentioning
confidence: 83%
“…This ''parietal old/new effect'' is maximal over centro-posterior scalp sites and takes the form of a positive shift to repeated pairs (Donaldson & Rugg, 1998Weyerts et al, 1997, but see Tsivilis et al, 2001). It has been proposed, and intracranial recordings have provided data to support (e.g., Dietl et al, 2005;Trautner et al, 2004), that this late positive complex, hereafter referred to as the LPC, reflects processing in medial temporal lobe structures (i.e., hippocampus). 1 To date, no experiment has provided evidence for ERP effects earlier than the LPC that distinguish between maintained and rearranged pairs of items.…”
Section: Introductionmentioning
confidence: 99%